2008
DOI: 10.3727/096368908786576516
|View full text |Cite
|
Sign up to set email alerts
|

Mature Adipocyte-Derived Cells, Dedifferentiated Fat Cells (DFAT), Promoted Functional Recovery from Spinal Cord Injury-Induced Motor Dysfunction in Rats

Abstract: Transplantation of mature adipocyte-derived cells (dedifferentiated fat cells) led to marked functional recovery from spinal cord injury (SCI)-induced motor dysfunction in rats. When mature adipocytes were isolated from rat adipose tissue and grown in ceiling culture, transformation into fibroblast-like cells without lipid droplets occurred. These fibroblast-like cells, termed dedifferentiated fat cells (DFAT), could proliferate and could also differentiate back into adipocytes. DFAT expressed neural markers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 43 publications
4
53
0
Order By: Relevance
“…6 and Fig. 7), as reported previously by others [14,16,18,20,32]. We used the huADSC generated from the fat tissue of a 65-year-old donor to treat ICH inflicted rats and evaluated functional behavior of the rats for 28 days.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…6 and Fig. 7), as reported previously by others [14,16,18,20,32]. We used the huADSC generated from the fat tissue of a 65-year-old donor to treat ICH inflicted rats and evaluated functional behavior of the rats for 28 days.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have indicated that human adipose-derived adult stem cells are a population of mesenchymal stem cells and demonstrated differentiation of stem cells into adipocytes, chondrocytes, myocytes, osteoblasts and neural progenitor cells after chemical inductions [14,16,18,20,32]. Transplantation of matured adipocyte-derived cells and dedifferentiated fat cells to promote functional recovery from spinal cord injury-induced motor dysfunction in rats was reported [20] and an attempt of cellular therapy employing human adipose tissue-derived stromal cells for rats with cerebral ischemia after MCAO resulted in significant functional improvement [17]. We found that the huADSC consist of innate neural stem cells in addition to MSCs based on our observation that the huADSC expressed neural β-III tubulin, nestin, GFAP and MAP2 proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,38) Cell replacement therapy is currently attracting attention as a potentially attractive strategy for the treatment of neurodegenerative diseases including SCI. Am-80 combined with cell therapy 42) might provide a new strategy for SCI.…”
Section: )mentioning
confidence: 99%
“…Exploiting the stem cell capacity of DFAT cells, many groups have investigated their potential to treat or improve various diseases 8,9 . Improvements of pathologic conditions, such as infracted cardiac tissue, spinal cord injury and urethral sphincter dysfunction, have been observed with DFAT cell injections in rat models of disease [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%